AB0357 Pregnancy outcomes of rheumatic patients with pre/peri gestational leflunomide exposure. (23rd January 2014) - Karadag, O.; Kilic, L.; Erbil, A. A.; Yılmaz, N.; Akdogan, A.; Kalyoncu, U.; Bilgen, S. A.; Kiraz, S.
Abstract : Background: Leflunomide is a frequently used disease modifying drug in rheumatoid arthritis, psoriatic arthritis, vasculitis etc. Findings from animal studies have suggested that leflunomide may be a human teratogen and a wash out protocol is required for patients before planning pregnancy. Data about pregnancy in patients with leflunomide exposure is limited with case reports and case series. Objectives: This study is aimed to evaluate the outcomes of pregnancies in patients with leflunomide exposure. Methods: Hospital files between years of 2004-2012 were used for selecting patients who used leflunomide before or during pregnancy. In addition to demographic and clinical characteristics of patients, a study form consist of -drugs usedbefore pregnancy, elimination application, duration of pregnancy, drug use and pregnancy outcomes- is filled. Totally 33 patients (female /male: 24/9) were included into the study. Results: In 12 of 33 patients (36.4%) no pregnancy occurred during more than 1 year follow up. Pregnancy took place in 16 (66.7%) of female and 5 (55.6%) of male patients' wives while in others no pregnancy occurred Bloods levels of leflunomide were examined in 19 of 21 pregnancies. Leflunomide washout protocol with cholestyramine was applied in 15 patients. In 13 of female patients leflunomide was interrupted before pregnancy but in 3 patients it was stopped after detection of pregnancy. Results and the complications of pregnancies were shown in Table 1 . Anti-Tumor necrosis factor (Anti-TNF) usage was positive in 4 of them – one of them had used during pregnancy. Majormalformations were not detected in any infants. Premature membrane rupture was observed in wife of a male patient. Conclusions: Observation of none pregnancy in more than one third of patients during >1 year follow up, might reflect that rheumatic patients on leflunomide treatment had an increased reproductive problems. Wash out protocol and assessing blood drug level are used in most of patients before planning pregnancy. Althoughwe experienced no major malformations, the rate of complications such as premature rupture of membrane and low birth weight were higher. To give rise to more precise data, methods of contraception should be advised in patients receiving leflunomide. Disclosure of Interest: None Declared